Types of impression materials that are effective for use in the fabrication of dentures: Jenis bahan cetak yang efektif digunakan dalam pembuatan gigi tiruan - Indriani, Lenni; Salsabila, Nurul; Rading, Fahmi; Maudina, Aura; Khoirunnisa, Aulia (Makassar Dental Journal, 2025)
Dental impressioning aims to produce accurate moulds of teeth and oral tissues. Impression materials and moulds must meet cri-teria such as precision, non-toxicity, and adequate setting time. Selecting the appropriate impression material is crucial for pro-ducing accurate and high-quality dental prostheses. This study discusses various types of impression materials, both elastic and non-elastic, and identifies the most effective materials for making dental prostheses. Polyvinylsiloxane (PVS) is the most widely used and most accurate impression material compared to others, as PVS has high dimensional stability, superior accuracy, and good elastic recovery. It is concluded that ongoing education and training on materials and impression techniques are essential to achieve optimal results.